Temporal Trends in Colorectal Cancer Associated With Type 2 Diabetes Mellitus in U.S. Adults, 1999–2023: A CDC Wonder Database Analysis—A Population‐Based Cross‐Sectional Study - Waleed Tariq; Neha Waseem; Mehreen Maka; Bushra Ubaid; Sheetal Verma; Yusra Ejaz; Maryam Owais; Awais Tariq; Soha Waseem; Iftikhar Khan; Ehsanullah Alokozay; Muhammad Hassan Tariq; et al. (Health Science Reports, 2026)
ABSTRACT Background and Aims Colorectal cancer (CRC) and type 2 diabetes mellitus (T2DM) are significant contributors to global morbidity and mortality, with growing evidence suggesting a synergistic impact on disease outcomes. This research focused on analyzing trends in CRC‐related deaths among individuals with coexisting T2DM in the United States from 1999 to 2023, as well as exploring disparities among different demographic and geographic groups. Methods Data were obtained from the CDC WONDER database for deaths among adults aged ≥ 45 years with CRC as the underlying cause and T2DM as a contributing cause. Age‐adjusted mortality rates (AAMRs) per 100,000 population were calculated using the 2000 U.S. standard population. Temporal trends were analyzed using Joinpoint regression to estimate annual percent change (APC) and average annual percent change (AAPC) with 95% confidence intervals (CI). A two‐sided p < 05 was considered statistically significant. Results From 1999 to 2023, there were 22,392 recorded deaths. The overall age‐adjusted mortality rate (AAMR) increased from 0.55 to 1.04 per 100,000 people, with an average annual percentage change (AAPC) of 2.55% (95% CI: 2.18–3.06; p < 001). Men experienced higher mortality rates than women, and individuals aged ≥ 65 years had higher rates than those aged 45–64. Significant racial disparities were evident, with the highest AAMRs among Hispanic and non‐Hispanic Black groups. Geographically, the West had the highest AAMRs and the steepest increase over time. Rural areas consistently showed higher AAMRs compared to urban areas. Most deaths (44.06%) occurred at home. Conclusion CRC‐related mortality in individuals with coexisting T2DM has risen sharply in the US over the past twenty years, showing significant demographic and geographic differences. These results highlight the importance of implementing targeted, integrated prevention and management approaches to decrease the combined impact of CRC and T2DM. The Detailed Visual Abstract is illustrated in the Central Illustration.